Selection parameters and yield enhancement of upload cotton (Gossypiunz hirsutum) under irrigated ecosystem of north India - TUTEJAJ, O P; KUMAR, SUNIL; SINGH, MAHENDAR (The Indian Journal of Agricultural Sciences, 2011)
An investigation was taken up during rainy season in 2000-0 I to detennine the interrelationship between quantitative traits and seed yield cotton and their direct and indirect effects on seed cotton yield. Six female (lines) of well adaptive cultivars and 9111ales (testers) atten1pted in a line x tester fashion in upland cotton were grown in randonlized block designs with 3 replications. Selection parameters, correlation studies aillong seed cotton yield and its related traits, the cause and effect relationships were studied for 8 characters. The characters except seed cotton yield and 2.5 % span length shothat phenotypic variation had considerably higher value than the genotypic variation. Seed cotton yield had showed high heritablity (90.47 %) coupled with high genetic advance (762.21) revealed that this trait has high capacity from parents to next generation. Whereas 2.5 %span length had high heritability (93.62 %) coupled with low genetic advance indicate that this trait .have high capacity to transfer from one generation to next generation. Association and direct contribution of different characters towards the seed cotton yield revealed that plant height and nunlber ofbolls/plant exhibited significant positive association with seed cotton yield. Due weightage should also,to be given the char